La città e l'inconscio nell'era globale. Germanistica in dialogo interdisciplinare - Maletta, Rosalba (Milano University Press, 2023)
The City and the Unconscious in the Global Age. German Studies in Multidisciplinary Dialogue hosts many more questions than it is possible to state here and seeks answers that introduce an ethic of citizenship for the third millennium, where the goals of Agenda 2030 are not reduced to slogans and empty talks and where the grassroots activists do not risk to be hushed up or even taken in by the most powerful corporations, which pretend to operate in the acknowledgment of the differences that Otherness entails. The inspirers of the volume are German-speaking intellectuals, poets, artists, architects from various backgrounds. In particular, we started from the ideas and work of Bruno Taut to rethink through Sigmund Freud, F. G. Jünger, Paul Celan, Durs Grünbein and many others social bonding in the age of anthropological mutation and pandemic emergencies.